Tricuspid regurgitation velocity and other biomarkers of mortality in children, adolescents and young adults with sickle cell disease in the United States: The PUSH study. Issue 7 (21st April 2020) - Nouraie, Mehdi; Darbari, Deepika S.; Rana, Sohail; Minniti, Caterina P.; Castro, Oswaldo L.; Luchtman‐Jones, Lori; Sable, Craig; Dham, Niti; Kato, Gregory J.; Gladwin, Mark T.; Ensing, Gregory; Arteta, Manuel; et al.
Abstract: In the US, mortality in sickle cell disease (SCD) increases after age 18‐20 years. Biomarkers of mortality risk can identify patients who need intensive follow‐up and early or novel interventions. We prospectively enrolled 510 SCD patients aged 3‐20 years into an observational study in 2006‐2010 and followed 497 patients for a median of 88 months (range 1‐105). We hypothesized that elevated pulmonary artery systolic pressure as reflected in tricuspid regurgitation velocity (TRV) would be associated with mortality. Estimated survival to 18 years was 99% and to 25 years, 94%. Causes of death were known in seven of 10 patients: stroke in four (hemorrhagic two, infarctive one, unspecified one), multiorgan failure one, parvovirus B19 infection one, sudden death one. Baseline TRV ≥2.7 m/second (>2 SD above the mean in age‐matched and gender‐matched non‐SCD controls) was observed in 20.0% of patients who died vs 4.6% of those who survived ( P = .012 by the log rank test for equality of survival). The baseline variable most strongly associated with an elevated TRV was a high hemolytic rate. Additional biomarkers associated with mortality were ferritin ≥2000 μg/L (observed in 60% of patients who died vs 7.8% of survivors, P < .001), forced expiratory volume in 1 minute to forced vital capacity ratio (FEV1/FVC) <0.80 (71.4% of patients who died vs 18.8% of survivors, P < .001), and neutrophil count ≥10x10 9 /L (30.0% of patients who died vs 7.9% of survivors, P = .018). In SCD children, adolescents and young adults, steady‐state elevations of TRV, ferritin and neutrophils and a low FEV1/FVC ratio may be biomarkers associated with increased risk of death.